1992
DOI: 10.1163/156856192x00043
|View full text |Cite
|
Sign up to set email alerts
|

Glass fiber surface effects in silane coupling

Abstract: Glass fibers with the nominal E-glass composition were synthesized with 0, 2, 4, or 6% B2.O3. The influence of the H2O3 content on aminosilane adsorption was evaluated using X-ray photoelectron spectroscopy (XPS) and zeta potential measurements. The water adsorption capacity of the silane-treated fibers was measured using a gravimetric technique. It was found that the presence of B2O3 enhanced the adsorption of aminosilane, but, more significantly, it greatly increased the water adsorption capacity of the sila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Aluminium ions are leached from the surface of E-glass fibers by the action of the acetic acid used to adjust the pH of aqueous silane solutions (4,14). The majority of surface silanols are involved in a highly cross-linked Si-O-Si network, which provides a hydrophobic outer surface, having a surface charge similar to that of the untreated E-glass.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium ions are leached from the surface of E-glass fibers by the action of the acetic acid used to adjust the pH of aqueous silane solutions (4,14). The majority of surface silanols are involved in a highly cross-linked Si-O-Si network, which provides a hydrophobic outer surface, having a surface charge similar to that of the untreated E-glass.…”
Section: Introductionmentioning
confidence: 99%
“…An increased uptake of water was observed for APTES d200 p300 and p350 although these samples did not adsorb nitrogen and have to be described as nonporous in terms of open pores larger than the diameter of N 2 (reported between about 0.3 and 0.4 nm) [38][39][40]. Therefore it can be assumed that another sorption mechanism like chemisorption, rearrangement reactions or swelling takes place [41].…”
Section: Discussionmentioning
confidence: 92%
“…Because B 2 O 3 reacts exceedingly with water, hydrolytic degradation of the glass fiber might occur, splitting the supporting network of the glass. Therefore, B 2 O 3 on the glass fiber surface might increase the hydrolytic degradation and negatively influence the polymer-fiber system (23). In a previous study by Vallittu (22), the amount of B 2 O 3 was reported to be higher in Stick-Net when compared with other glass fiber systems.…”
Section: Discussionmentioning
confidence: 95%
“…Woven fibers embedded in composites are widely used in periodontal splints, orthodontic retainers, endodontic posts, and fixed partial dentures (19)(20)(21)(22)(23) for reinforcement. Because these fibers vary in their chemical and physical properties as well as in their fabric configurations (19), their application areas might be different.…”
Section: Discussionmentioning
confidence: 99%